The influence of non-ideal phase flow on the extraction efficiency for the case of a linear equilibrium distribution - Tadić G.; Gligorić M.; Tolić A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The influence of the fundamental parameters of non-ideal phase flow and the extraction parameters on the number of equilibrium stages - ND, theoretical stages - NT, as well as the number of stages (ND - NT), the existence of which is a consequence of the backflow in extractors, was investigated. The calculated number of stages (ND - NT) served as a measure of the influence of the denoted parameters on the extraction efficiency. The results of the investigation indicate that the number of stages (ND - NT) considerably increased with increasing backmixing coefficients and that the dependence was linear. It was established that the increase of the ratio of the flow rate of the heavy and light phase and the decrease of the equilibrium distribution coefficient, as well as the increase of the total separation factor, led to an exponential increase of the number of stages in the extractor, which consequently caused a decrease in the extraction efficiency.